More invaders do not result in heavier impacts: The effects of non‐native bullfrogs on native anurans are mitigated by high densities of non‐native crayfish. (22nd January 2018) - Liu, Xuan; Wang, Supen; Ke, Zunwei; Cheng, Chaoyuan; Wang, Yihua; Zhang, Fang; Xu, Feng; Li, Xianping; Gao, Xu; Jin, Changnan; Zhu, Wei; Yan, Shaofei; et al.
Abstract: With accelerating species introductions in an era of globalization, co‐occurring alien species have become increasingly common. Understanding the combined ecological impacts of multiple invaders is not only crucial for wildlife managers attempting to ameliorate biodiversity loss, but also provides key insights into invasion success and species coexistence mechanisms in natural ecosystems. Compared with much attentions given to single‐invader impacts, little is known about the impacts of multiple co‐occurring invaders. The American bullfrog ( Lithobates catesbeianus  =  Rana catesbeiana ) and the red swamp crayfish ( Procambarus clarkii ) are two aquatic invasive species in many different areas of the globe. They coexist with native anurans in a variety of permanent lentic waters, which provide an ideal model system to explore the combined effects of multiple invaders from different trophic levels on native species. Based on a global diet analysis covering 34 native and invasive bullfrog populations, and data from 10‐year field surveys across 157 water bodies in the Zhoushan Archipelago, China, we observed a reduced impact of bullfrogs on native anurans at high crayfish densities when the two invaders co‐occurred. The global diet analysis showed that crayfish occurrence reduced the number of native anuran prey consumed by bullfrogs in both native and invasive populations. After accounting for pseudoreplication of different observations among water bodies, islands, and survey time, model averaging analyses based on GLMMs showed a negative relationship between bullfrog density and native anuran densities for field observations of invasive bullfrogs alone and co‐invaded observations with low crayfish density. However, this negative relationship disappeared when the two invaders co‐occurred with high crayfish density. Structural equation modelling ( SEM ) analyses further validated that the impacts of bullfrogs on native frogs were mitigated by the negative interactions between crayfish and bullfrogs. Our results provide novel evidence of a density‐dependent antagonistic effect of two sympatric invaders from different trophic levels on native species. This study highlights the importance of considering complex interactions among co‐invaders and native species when prioritizing conservation and management actions and will facilitate the development of a more precise framework to predict invasion impacts. Abstract : This paper represents a novel and important contribution to the ecological literature because it is the first to test the combined effects of two global invaders with different trophic positions on other native species by linking long‐term field data in China and global trophic niche analyses.